2014
DOI: 10.1038/ki.2013.327
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesemia is a significant predictor of cardiovascular and non-cardiovascular mortality in patients undergoing hemodialysis

Abstract: Although previous studies in the general population showed that hypomagnesemia is a risk for cardiovascular diseases (CVD), the impact of magnesium on the prognosis of patients on hemodialysis has been poorly investigated. To gain information on this we conducted a nationwide registry-based cohort study of 142,555 hemodialysis patients to determine whether hypomagnesemia is an independent risk for increased mortality in this population. Study outcomes were 1-year all-cause and cause-specific mortality with bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
287
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(319 citation statements)
references
References 44 publications
19
287
4
2
Order By: Relevance
“…Similarly, secondary calciprotein particles induce calcification in vitro, and Mg prolongs the time until formation of secondary calciprotein particles in serum (4). This suggests that the inverse association between serum Mg and cardiovascular events (16) and the in vivo inhibitory effect of Mg supplementation on vascular calcification (17) might be due to the inhibitory effect of Mg on amorphous Ca/PO 4 transformation (12) and thus, inhibition of hydroxyapatite and calciprotein particle formation, which in turn, might prevent the formation of calcification. More studies are needed to further examine this association in humans.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, secondary calciprotein particles induce calcification in vitro, and Mg prolongs the time until formation of secondary calciprotein particles in serum (4). This suggests that the inverse association between serum Mg and cardiovascular events (16) and the in vivo inhibitory effect of Mg supplementation on vascular calcification (17) might be due to the inhibitory effect of Mg on amorphous Ca/PO 4 transformation (12) and thus, inhibition of hydroxyapatite and calciprotein particle formation, which in turn, might prevent the formation of calcification. More studies are needed to further examine this association in humans.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, low serum magnesium levels were associated with higher all-cause mortality in Japanese dialysis patients (20), but few data exist on SCD risk and magnesium dialysate levels.…”
Section: Role Of Dialysis Bathsmentioning
confidence: 99%
“…In our study, we found that hypermagnesemia (42.5 mg/dL) occurs in up to 44% of cases. Although the previous studies were largely concerned about the role of hypomagnesaemia and suggested that hypomagnesaemia was a predictor of mortality in patients undergoing hemodialysis, 26 it was also worthy to note that the association between serum magnesium level and mortality is potentially J-shaped. Thus, hypermagnesemia and its effect on prognosis in hemodialysis patients could not be ignored either.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Recently, since numerous studies suggested an association between hypomagnesaemia and risk factors of cardiovascular disease, such as diabetes mellitus, metabolic syndrome, coronary artery disease and atherosclerosis risk in the general population, 24,25 the impact of magnesium disorders on the prognosis of patients with chronic kidney disease has received a great deal of interest. Although clinical and epidemiological studies have consistently suggested that lower serum magnesium levels were associated with vascular calcification and cardiovascular mortality among patients with end-stage renal disease (ESRD), 19,[26][27][28] the pathophysiology and the role of magnesium disturbances in chronic kidney disease still need further studies.…”
Section: Discussionmentioning
confidence: 99%